Overcoming Resistance to Immune Checkpoint Blockade in Liver Cancer with Combination Therapy: Stronger Together? - Werner, Wiebke; Kuzminskaya, Maria; Lurje, Isabella; Tacke, Frank; Hammerich, Linda (Seminars in Liver Disease, 2024)
Primary liver cancer, represented mainly by hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (CCA), is one of the most common and deadliest tumors worldwide. While surgical resection or liver transplantation are the best option in early disease stages, these tumors often present in advanced stages and systemic treatment is required to improve survival time. The emergence of immune checkpoint inhibitor (ICI) therapy has had a positive impact especially on the treatment of advanced cancers, thereby establishing immunotherapy as part of first-line treatment in HCC and CCA. Nevertheless, low response rates reflect on the usually cold or immunosuppressed tumor microenvironment of primary liver cancer. In this review, we aim to summarize mechanisms of resistance leading to tumor immune escape with a special focus on the composition of tumor microenvironment in both HCC and CCA, also reflecting on recent important developments in ICI combination therapy. Furthermore, we discuss how combination of ICIs with established primary liver cancer treatments (e.g. multikinase inhibitors and chemotherapy) as well as more complex combinations with state-of-the-art therapeutic concepts may reshape the tumor microenvironment, leading to higher response rates and long-lasting antitumor immunity for primary liver cancer patients.
Keywords: hepatocellular carcinoma; cholangiocarcinoma; immunotherapy; checkpoint inhibitors; resistance